The return [compact disc, unabridged] : an Inspector van Veeteren mystery - Nesser, Håkan, 1950- (Nesser, Håkan, 1950- Inspector Van Veeteren mystery., 2011)
When a young girl on a woodland hike stumbles upon a corpse with no hands, feet, or head, Chief Inspector Van Veeteren, recovering from surgery in a nearby hospital, begins to piece together the clues in the case.